Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

If [tex]\( f(x) = 2x - 3 \)[/tex], [tex]\( g(x) = \frac{2x - 7}{3} \)[/tex], and [tex]\( f(f(x)) = g^{-1}(x) \)[/tex], find the value of [tex]\( x \)[/tex].

Answer: [tex]\( x = 5 \)[/tex]


Sagot :

Certainly! Let's solve the given problem step-by-step.

Given:
1. [tex]\( f(x) = 2x - 3 \)[/tex]
2. [tex]\( g(x) = \frac{2x - 7}{3} \)[/tex]

We are given the equation [tex]\( f(f(x)) = g^{-1}(x) \)[/tex] and need to find the value of [tex]\( x \)[/tex].

### Step 1: Calculate [tex]\( f(f(x)) \)[/tex]

First, we need to find [tex]\( f(f(x)) \)[/tex]:
[tex]\[ f(f(x)) = f(2x - 3) \][/tex]
To do this, we substitute [tex]\( 2x - 3 \)[/tex] into the function [tex]\( f \)[/tex] again:
[tex]\[ f(2x - 3) = 2(2x - 3) - 3 \][/tex]
[tex]\[ = 4x - 6 - 3 \][/tex]
[tex]\[ = 4x - 9 \][/tex]
Thus, [tex]\( f(f(x)) = 4x - 9 \)[/tex].

### Step 2: Find the inverse of [tex]\( g(x) \)[/tex]

Next, we need to find the inverse of [tex]\( g(x) \)[/tex]. Let [tex]\( y = g(x) \)[/tex]:
[tex]\[ y = \frac{2x - 7}{3} \][/tex]
To find the inverse, we solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = \frac{2x - 7}{3} \][/tex]
Multiply both sides by 3:
[tex]\[ 3y = 2x - 7 \][/tex]
Add 7 to both sides:
[tex]\[ 3y + 7 = 2x \][/tex]
Divide both sides by 2:
[tex]\[ x = \frac{3y + 7}{2} \][/tex]
Thus, the inverse function [tex]\( g^{-1}(x) \)[/tex] is:
[tex]\[ g^{-1}(x) = \frac{3x + 7}{2} \][/tex]

### Step 3: Set up the equation [tex]\( f(f(x)) = g^{-1}(x) \)[/tex]

We have [tex]\( f(f(x)) = 4x - 9 \)[/tex] and [tex]\( g^{-1}(x) = \frac{3x + 7}{2} \)[/tex].

Set them equal to each other:
[tex]\[ 4x - 9 = \frac{3x + 7}{2} \][/tex]

### Step 4: Solve for [tex]\( x \)[/tex]

To eliminate the fraction, multiply both sides by 2:
[tex]\[ 2(4x - 9) = 3x + 7 \][/tex]
[tex]\[ 8x - 18 = 3x + 7 \][/tex]

Subtract [tex]\( 3x \)[/tex] from both sides:
[tex]\[ 8x - 3x - 18 = 7 \][/tex]
[tex]\[ 5x - 18 = 7 \][/tex]

Add 18 to both sides:
[tex]\[ 5x = 25 \][/tex]

Divide by 5:
[tex]\[ x = 5 \][/tex]

### Conclusion

The solution to the given equation [tex]\( f(f(x)) = g^{-1}(x) \)[/tex] is:

[tex]\[ \boxed{5} \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.